Materialism In Modern Education: A Philosophical Analysis And Theological Criticism From The Perspective Of Christian Religious Education - Pada, Marniati; Kake, Yada Jufenta; Talan, Lidia; Banu, Maher (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Materialism is a philosophical school that views matter as the highest reality and rejects the existence of the spiritual dimension. This view has had a major influence on the development of modern science and education, especially in the emphasis on cognitive, empirical aspects and measurable achievements. This article aims to examine the basic concept of materialism, the main figures who influence it, and the implications of its application in the world of education. Furthermore, this article critically analyzes materialism from the perspective of Christian faith and Christian Religious Education (PAK). Through a literature review approach and theological analysis, it was found that materialism has made a positive contribution to the development of scientific methods, but at the same time has serious weaknesses because it reduces humans to purely physical creatures. This view is contrary to the teachings of the Bible which emphasizes humans as God's creation who have a body, soul and spirit. Therefore, this article recommends that Christian Religious Education develop a holistic educational approach by integrating cognitive, moral and spiritual aspects, so that students are not trapped in a materialistic mindset